Beautiful darkness - Garcia, Kami.; Stohl, Margaret; Penguin Books (London : Penguin Books, 2013)
In a small southern town with a secret world hidden in plain sight, sixteen-year-old Lena, who possesses supernatural powers and faces a life-altering decision, draws away from her true love, Ethan, a mortal with frightening visions.
Young Adult.
Young Adult
Keywords: Psychic ability -- Juvenile fiction; Supernatural -- Juvenile fiction; Love -- Fiction; Psychic ability -- Fiction; Supernatural -- Fiction; Love stories; Parapsychology -- Fiction; Supernatural -- Fiction; South Carolina -- Juvenile fiction; South Carolina -- Fiction; South Carolina -- Fiction; Love stories